Post-Islamisme dan Gerakan Politik Islam Dalam Sistem Demokrasi Indonesia - Bani Syarif Maula (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2019)
Indonesia is a country with a majority Muslim population that implements a democratic system. Based on this democratic system, non-muslims constitutional systems can coexist and play an active role in carrying out religious values in the public sphere as a very visible feature. Nonetheless, the relationship between Islam and the state in the course of Indonesian history always experiences ups and downs. In one period of Indonesian history, Islamic politics was a peripheral thought and movement and even considered a threat to democracy and the value of modernity, because Islamic groups struggled to maintain the ideology of Islamism with the aim of establishing an Islamic state, or at least implementing a traditional Islamic legal system to a modern Indonesian society. However, as the development of the Islamic world coincided with efforts to democratize the Indonesian state, Islamic politics also changed its direction to adjust to these conditions. Islamic groups become more accommodating to the values of democracy and modernity, without having to leave their Islamic identity. This last phenomenon is known as post-Islamism as a socio-political movement in the life of the nation and state in Indonesia.